State Responsibility for Environmental Protection during International Armed Conflict - Afriansyah, Arie (Indonesian Journal of International Law, 2011)
In the last ten decades, many international armed conflicts have occurred bringing not only human casualties but also deleterious environmental damages. It is widely acknowledged that the environment is frequently both being the victim and a tool of armed conflict. Some further argue that attacking the environment, as a means of waging war, is not a new concept. These arguments show that the environment eventually plays an important role during warfare. Given these facts, the international community doubts the effectiveness of humanitarian law to prevent environmental devastation during international armed conflict. It then considers the relevance in applying peacetime obligations to protect the environment in particular to common goods and areas beyond national jurisdiction to strengthen the rules on the law of war. As damage to the environment might be unavoidable, it can be argued that reparation as the form of State responsibility of the warring parties is worth to pursuit. It is based on the fact that belligerents have international obligations to protect the environment during armed conflict that come from not only wartime but also peacetime international law. It is submitted that violations to those rules will incur international state responsibility for all of the conflicting parties. This study tries to examine the implementation of the applicable laws during armed conflict in protecting the environment. It then analyses the implementation of state responsibility for any environmental damage after the end of the hostilities. This study will only focus on international armed conflict for its relevance to the concept of state responsibility. It will examine cases of World Wars I and II, Vietnam War, Persian Gulf War, and Lebanon-Israel War. They were chosen because they represent notable example of international armed conflicts in the last century with significant environmental calamities.